Effects of bismuth addition and electrodeposition processing on Zn-based coatings - Tay, S.L.; Wang, Y.; Wei, X.; Gao, W. (World Scientific Publishing, 2015)
Zn and Zn-Bi coatings were electroplated on mild steel substrate by direct and pulse current (PC) techniques. The effects of Bi and deposition method on the phase, microstructure and mechanical properties of Zn-based coatings have been studied. Results showed that the crystal orientation and microstructure of Zn-Bi coatings were different compared to the pure Zn coating. By adding a small amount of Bi solution into Zn electrolyte, the microhardness of Zn-Bi coatings was increased by two times, and the wear volume loss was also decreased. Finer grain size and smoother surface can be achieved by utilizing PC deposition, resulting in better mechanical properties compared to the direct current (DC) deposition.